Variation in responses to boron in rice - Lordkaew S. (2014)
Background and aims: Boron (B) deficiency depresses grain set and grain yield of wheat and maize while having little effect on their vegetative growth. This paper describes effects of B deficiency in rice and how these vary with planting season and variety. Methods: Three rice varieties (KDML105, CNT1, SPR1) were grown in sand culture without (B0) and with 10 μM (B10) B added to the nutrient solution, in the cool season of 2007/08 and 2008/09 and the hot season of 2011 in Chiang Mai, Thailand (18°47′N, 98°59′E). Boron responses were measured in growth and yield parameters, pollen viability and B concentration of the flag leaf and anthers at anthesis. Results: Grain weight was strongly depressed by B deficiency ranging from 28 % in SPR1 to 79 % in CNT1, and the yield was much lower in the cool season than in the hot season plantings. The variation in grain weight was closely associated with grain set and number of spikelets but not with shoot dry weight or tillering. Grain set was closely related to pollen viability, and both were increased with increasing anther B concentration at >20 mg B kg-1. In addition to its adverse effect on grain set, B deficiency also depressed grain filling and weight of individual grains in rice. Conclusions: Boron deficiency depressed rice grain yield through adverse effects on reproductive growth, panicle and spikelet formation and grain filling, in addition to grain set as in wheat and maize. © 2012 Springer Science+Business Media B.V.